Successful Treatment of a Patient With Multiple-Line Relapsed Extensive-Stage Small-Cell Lung Cancer Receiving Penpulimab Combined With Anlotinib: A Case Report - Zhang, Zibo; Li, Yujun; Dong, Yan; Li, Jia; Zhang, Bin; Zhang, Chunxia; Cui, Xiaonan (Frontiers in Oncology, 2022)
Small-cell lung cancer (SCLC) is a group of disease with high malignancy, poor biological behavior and rapid development. Most patients had extensive-stage SCLC (ES-SCLC) when they were firstly diagnosed. Standard chemotherapy is prone to relapse in a short period of time and the median overall survival (OS) can only reach 13 months in combination with PD-L1 inhibitors. Up to now, there are no studies to verify efficacy and safety of the composite treatment of ES-SCLC with penpulimab and anlotinib in spite of some recognized data and advantages related to combined regimen. Penpulimab is a novel PD-1 inhibitor with a sub-type of IgG1, has a structural modification of the Fc segment which can prevent immune cells from being swallowed or killed and avoid tumor immune escape steadily. This case report will introduce a 71-year-old male who has suffered from ES-SCLC for 7 years and progressed after receiving standard systemic chemotherapy combined with radiotherapy. The third-line treatment for 4 cycles with anlotinib and carrilizumab was discontinued due to grade 2 immune-related pneumonia despite the efficacy was evaluated as stable disease (SD). After maintaining the 22-month progression-free survival (PFS), the patient relapsed and switched to the safer penpulimab combined with anlotinib to continue the treatment for 4 cycles. The partial response (PR) evaluation was confirmed twice and the patient remained in good general condition. Obviously, the combination with penpilimab and anlotinib can positively regulate therapeutic effect by acting simultaneously on the tumor microenvironment and promoting normalization of blood vessels. In general, this case proves the successful possibility of re-challenge with immune checkpoint inhibitors (ICIs), the better clinical efficacy of cross-line therapy with anlotinib and the drug safety of penpulimab, which provides a highly meaningful therapy for the clinical treatment of ES-SCLC.